THE RELATIONSHIP BETWEEN INTEREST IN LEARNING AND LEARNING OUTCOMES IN MATHEMATICS IN BUILDING MATERIALS FOR 5TH GRADE STUDENTS AT SDN BAHAGIA 04 - Aldira Wibiyanti Putri; Dian Anggraeni Maharbid (Institut Pendidikan Indonesia, 2023)
This study aims to determine whether there is a relationship between interest in learning and learning outcomes in mathematics in the materials for 5th Grade Students at SDN Bahagia 04.The population in this study was all fifth grade students at SDN Bahagia 04. The sample in this study consisted of 50 people. Sampling using random sampling technique. The measuring instrument used in this study was a Likert scale which was carried out with a questionnaire sheet instrument to measure interest in learning and a test instrument to collect data on learning outcomes. The data analysis technique used is Product Moment correlation. Prerequisite test of data analysis in the form of normality test and linearity test. Data analysis techniques and data analysis prerequisite tests were carried out using SPSS26. The results showed that: (1) the learning interest of fifth grade students at SDN Bahagia 04 based on a mean of 68.56 was in the moderate category with a proportion of 48%, (2) student learning outcomes in mathematics in geometric material based on the KKM value of 75 with an average of 8.72 is in the incompetent category with a percentage of 44%, (3) there is a positive and significant relationship between learning interest (X) and learning outcomes (Y) math material for class V SDN Bahagia 04 with a significance level of 5% the value of “r” count is greater than “r” table (0.721 > 0.279).